Art/Research: Working the Slash - Conrad, Diane; Leavy, Patricia (Art/Research International, 2025)
In this short, invited piece for the journal’s 10th anniversary issue, co- founding editors of Art/Research International, Diane Conrad and Patricia Leavy, reflect upon their experiences of envisioning an open access online journal for the publication of creative scholarly research. The journal that evolved realized the inclusive forum they sought to showcase through international and transdisciplinary scholarship that embraced the myriads of creative forms and provocative themes authors were exploring. They are honoured to have played a role in bringing Art/Research to life.